Pendidikan Sosial Berbasis Kearifan Lokal: Penguatan Nilai-Nilai Siri’ na Pacce pada Generasi Muda di Desa Bontomanai, Kecamatan Bungaya, Kabupaten Gowa - Rosdiana Rosdiana; Muhammad Afdal (Jurnal Pelayanan Masyarakat, 2026)
This community service program addresses the decline of local wisdom values of Siri’ na Pacce among younger generations due to modernization and foreign cultural influences. Siri’ na Pacce represents the cultural foundation of Makassar society, emphasizing self-esteem, honesty, and social solidarity, which are essential for maintaining social harmony. The program aims to identify youth understanding of these values, develop social education based on local wisdom, and enhance awareness and application in daily life. A participatory approach was applied, including initial observation, material development, interactive workshops, discussions, mentoring, and evaluation. The program involved 40 purposively selected youths from Bontomanai Village, Bungaya District, Gowa Regency, an agrarian community experiencing cultural shifts. The results indicate improved understanding of Siri’ na Pacce, increased critical awareness of globalization’s impact, and stronger internalization of cultural values in social interactions. Additionally, cultural preservation initiatives emerged through creative media. In conclusion, social education based on Siri’ na Pacce is effective in strengthening youth character rooted in cultural identity while mitigating negative effects of modernization. Continuous mentoring and integration of local values into formal and non-formal education are recommended.